Near-infrared monitoring of the accretion outburst in the massive young stellar object S255-NIRS3. (20th November 2019) - Uchiyama, Mizuho; Yamashita, Takuya; Sugiyama, Koichiro; Nakaoka, Tatsuya; Kawabata, Miho; Itoh, Ryosuke; Yamanaka, Masayuki; Akitaya, Hiroshi; Kawabata, Koji; Yonekura, Yoshinori; Saito, Yu; Motogi, Kazuhito; et al.
Abstract: We followed up the massive young stellar object S255-NIRS3 (= S255-IRS1b) during its recent accretion outburst event in the K_s band with Kanata/HONIR for four years after its burst and obtained a long-term light curve. This is the most complete near-infrared light curve of the S255-NIRS3 burst event that has ever been presented. The light curve showed a steep increase reaching a peak flux that was 3.4 mag brighter than the quiescent phase and then a relatively moderate year-scale fading until the last observation, similar to that of the accretion burst events such as EXors found in lower-mass young stellar objects. The behavior of the K_s -band light curve is similar to that observed in 6.7 GHz class II methanol maser emission, with a sudden increase followed by moderate year-scale fading. However, the maser emission peaks appear 30–50 d earlier than that of the K_s band emission. The similarities confirmed that the origins of the maser emission and the K_s -band continuum emission are common, as previously shown from other infrared and radio observations by Stecklum et al. (2016, Astronomer's Telegram, 8732), Caratti o Garatti et al. (2017b, Nature Phys., 13, 276), and Moscadelli et al. (2017, A&A, 600, L8). However, the differences in energy transfer paths, such as the exciting/emitting/scattering structures, may cause the delay in the flux-peak dates.